Mild Stress and Healthy Aging Applying hormesis in aging research and interventions - Le Bourg, Eric; Rattan, Suresh I.S (Springer Netherlands : Imprint: Springer, 2008)
Stress is a double edged sword. Whereas chronic stress has well known harmful effects, recent research shows that intermittent exposure of cells and organisms to mild stress can improve various biological parameters, including severe stress tolerance, health span and longevity. Mild stress-induced hormesis is potentially a powerful tool in gerontological research and interventions. This book brings together some of the world leaders in this area of research who present a critical analysis of the ongoing research with respect to the effects and mechanisms of action of various types of mild stress, such as irradiation, heat, physical exercise, hypergravity, pro-oxidants and nutritional components, on a variety of biological systems ranging from fruitflies to human cells and bodies. Their separate chapters and a final collective chapter open up a whole new world of possibilities for future research in aging, successful aging, and health span extension.